High school student group photograph - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
A group photograph of high school students. The studens sit and stand on the lawn in front of the school building. A sidewalk lined by palm trees is visible on the right. Several of the building windows are open.